NILAI- NILAI PANCASILA DALAM MENANGANI INTOLERANSI DI INDONESIA - Sapta Baralaska Utama Siagian (Jurnal Teologi Biblika, 2020)
There are two phenomena that emerged after the fall of the New Order regime and the 1998 reform era, namely the abolition of the socialization of the values ​​of Pancasila and the 1945 Constitution of the Republic of Indonesia in socio-political and social life, acts of radicalism and terrorism by radical groups. Psychologically, the social community is in a dilemma, leaving the old belief values ​​behind, but the new order values ​​are not yet available. The euphoria of freedom and reformation has led to the emergence of new understandings that are not necessarily in accordance with the values ​​of national and state life, one of which is the emergence of religious groups with radical views that encourage acts of violence, extremism and terrorism. The values ​​of Pancasila in the face of radicalism and terrorism, thus affecting ideological resilience which in turn has an impact on national resilience. Therefore we need an appropriate conception to overcome it.